Effect of cardamom powder and rosemary extract on textural, sensory, microbiological and colour properties of pinni during storage - Singh, Ravinder; Khamrui, Kaushik; Prasad, Writhdhama (Indian Journal of Dairy Science, 2020)
Pinni is an immensely popular milk cereal based composite sweet having dark brown colour with granular texture. The shelf life of pinni was studied by using natural preservatives i.e., cardamom powder and rosemary extract. Two packaging techniques viz., cardboard boxes and polystyrene tray were compared for sensory, textural, microbiological and colour quality of pinni during storage for 21 days and 28 days respectively at 30Â±1ËšC. The extent of loss of most sensory attributes was rapid in control samples packed in both packaging materials as compared to cardamom and rosemary extract added pinni samples. Based on the results obtained in the study it was concluded that pinni could be best preserved up to 28 days at room temperature (30Â±1ËšC) without appreciable quality loss and should be packed in polystyrene trays with rosemary extract and have shelf life 14 days more than control sample.